Relaxation behavior study on PET and PET/Ti3N4 nanocomposites. Issue 3 (24th March 2014) - Kang, Shenghong; Fei, Guangtao; Tian, Xingyou; Zheng, Kang; Zhang, Xian; Shui, Jiapeng
Abstract : The relaxation behavior of neat PET and PET/Ti3 N4 nanocomposites was investigated by means of internal friction. The temperature dependence of internal friction exhibit two relaxation peaks i.e. α and β peaks, and both heights of the peaks first increase and then decrease with increasing concentration of Ti3 N4 nanoparticles. However, the peak temperature and activation energy for α and β peaks show different change trends with increasing concentration of Ti3 N4 nanoparticles, which associated with the changes of nucleation and crystallization of the PET due to the addition of nanoparticles. Further increasing the concentration of Ti3 N4 nanoparticles, a third peak, α′ located at the temperature between α and β peaks appears in the PET/Ti3 N4 nanocomposites, which may be a physical aging peak.